Opportunities and Future Perspective of Nanofertilizers and Controlled Release Nanofertilizers in Agriculture - Tahereh Raiesi Ardali; Leila Soleimanpour; Leila Mamani; Mostafa Chorom (Journal of Water and Environmental Nanotechnology)
Nanofertilizers offer opportunities for the development of new types of fertilizers. In this study, we focused on the different types of nano fertilizers that enhance plant growth and reduce harmful environmental effects. Nanofertilizers, especially when using new technologies in fertilizer products such as nano-encapsulation and controlled release of nutrients, can increase plant nutrient uptake, enhance fertilizer efficiency, improve soil quality, and decrease environmental effects. This article discusses different types of nanofertilizers, including macronutrient nanofertilizers, micronutrient beneficial element nanofertilizers, novel technologies for fertilizer nutrients, and materials used in fertilizers. This article reviews literature using natural and synthetic coatings for the slow release of urea. The potential of environmentally friendly natural coatings compared to synthetic coatings has also been investigated. These composites, with excellent slow-release properties and non-toxicity to soil and environment, could be used in horticultural applications for higher agricultural production efficiency. Finally, this review suggests that nano fertilizers can increase crop production and reduce plant nutrient losses. Although the use of nanoparticles has many advantages, entering the global market requires more studies to investigate their comprehensive effects on the environment.